Jasmonates in plant growth and development and elicitation of secondary metabolites: An updated overview - Sohn, Soo-In; Pandian, Subramani; Rakkammal, Kasinathan; Largia, Muthiah Joe Virgin; Thamilarasan, Senthil Kumar; Balaji, Sekaran; Zoclanclounon, Yedomon Ange Bovys; Shilpha, Jayabalan; Ramesh, Manikandan (Frontiers in Plant Science, 2022)
Secondary metabolites are incontestably key specialized molecules with proven health-promoting effects on human beings. Naturally synthesized secondary metabolites are considered an important source of pharmaceuticals, food additives, cosmetics, flavors, etc., Therefore, enhancing the biosynthesis of these relevant metabolites by maintaining natural authenticity is getting more attention. The application of exogenous jasmonates (JAs) is well recognized for its ability to trigger plant growth and development. JAs have a large spectrum of action that covers seed germination, hypocotyl growth regulation, root elongation, petal expansion, and apical hook growth. This hormone is considered as one of the key regulators of the plant’s growth and development when the plant is under biotic or abiotic stress. The JAs regulate signal transduction through cross-talking with other genes in plants and thereby deploy an appropriate metabolism in the normal or stressed conditions. It has also been found to be an effective chemical elicitor for the synthesis of naturally occurring secondary metabolites. This review discusses the significance of JAs in the growth and development of plants and the successful outcomes of jasmonate-driven elicitation of secondary metabolites including flavonoids, anthraquinones, anthocyanin, xanthonoid, and more from various plant species. However, as the enhancement of these metabolites is essentially measured via in vitro cell culture or foliar spray, the large-scale production is significantly limited. Recent advancements in the plant cell culture technology lay the possibilities for the large-scale manufacturing of plant-derived secondary metabolites. With the insights about the genetic background of the metabolite biosynthetic pathway, synthetic biology also appears to be a potential avenue for accelerating their production. This review, therefore, also discussed the potential manoeuvres that can be deployed to synthesis plant secondary metabolites at the large-scale using plant cell, tissue, and organ cultures.